Effects of different protocols of physical exercise on fibromyalgia syndrome treatment: systematic review and meta-analysis of randomized controlled trials - Albuquerque, Maria Luiza L. (2022)
Physical exercise has been used as a form of treatment for fbromyalgia, however, the results indicate the need for further investigations on the efect of exercise on diferent symptoms. The aim of the study was to synthesize and analyse studies related to the efect of exercise in individuals with fbromyalgia and provide practical recommendations for practitioners and exercise professionals. A search was carried out in the Web of Science, PubMed, and Scopus databases in search of randomized clinical trials (RCT) written in English. A meta-analysis was performed to determine the efectiveness of different types of exercise on the fbromyalgia impact questionnaire (FIQ), and the protocol period and session duration on the pain outcome. Eighteen articles were eligible for a qualitative assessment and 16 were included in the meta-analysis. The exercise showed large evidence for the association with a reduction in the FIQ (SMD −0.98; 95% CI −1.49 to −0.48). Protocols between 13 and 24 weeks (SMD −1.02; 95% CI −1.53 to −0.50), with a session time of less than 30 min (SMD −0.68 95% CI −1.26 to −0.11) or>30 min and<60 min (SMD −1.06; 95% CI −1.58 to −0.53) presented better results. Better results were found after combined training protocols and aerobic exercises. It is suggested that exercise programs lasting 13–24 weeks should be used to reduce pain, and each session should last between 30 and 60 min. In addition, the intensity should always be carried out gradually and progressively